Using Homer Software for Cost Analysis of Stand-Alone Power Generation for Small Scale Industry in Nigeria: A Case Study Lumatec Aluminium Products - Luqman Raji; Zhigilla Y.I; Wadai J (Bandung State Polytechnic (Politeknik Negeri Bandung), 2021)
Nigeria is one of developing countries in the world that experience shortage of electricity for her economic and social development. In Nigeria, most of the small-scale industries use diesel/petrol-based systems to generate their electricity. However, due to the cost fluctuation of oil and gas fuel, an alternative power generation should be considered. This paper targets to examine the cost analysis of system for supplying electricity to LUMATEC Aluminium products shop in Mubi, Adamawa state Nigeria. Hybrid Optimization Model for Electric Renewable (HOMER) is used as a tool for cost analysis. The scenario consider in this study was only stand-alone with battery system. Results revealed that the system have 10kW PV with cost of electricity (COE) of 0.312/kW. The initial capital cost and total net present cost (NPC) are 21.775 and 26.148 respectively, with payback period of 5.8years. In conclusion, this study provides the solution of power supply to the small-scale industries at cost effective and available throughout the year and it is feasible to solve the small-scale industries, rural and urban electricity supplying in this country (Nigeria). It is recommended that Nigerian Government & Law makers should promotes the use of standalone PV system for domestic and small-scale industry by providing financial assistance through soft loans, subsides and grants.